Antinociceptive Properties of Hydro-Alcoholic Extract of Calendula Of.cinalis in Rat - Siamak Shahidi; Minoo Mahmoodi; Noushin Farahmandlou (Basic and Clinical Neuroscience, 2012)
Calendula Of.cinalis (Asteraceae) is widely used in traditional medicine as an anti-in.ammatory agent and has also been reported to have anti-bacterial, anti-fungal and anti-viral activities.  Sesquiterpene glycosides, saponins, triol, triterpenes and .avonoids are observed in its composition. The present study was designed to evaluate the antinociceptive effect of hydro-alcoholic extract of Calendula Of.cinalis in male rats. The animals were treated intraperitoneally with different doses of the Calendula Of.cinalis .ower extract (100, 150 and 250 mg/kg body weight). On the basis of the previous report the dose of 150 mg/kg is most effective. The analgesic activity was tested by tail .ick and acetic acid-induced writhing tests.  Data between experimental groups were compared by one way analysis of variance (ANOVA) followed by tukey’s as post hoc test. All doses of the extract and also naloxone + extract (150mg/kg) signi.cantly increased the tail .ick latency compared to the control group. The extract of Calendula of.cinalis signi.cantly reduced the number of abdominal constrictions and stretching of hind limbs induced by the injection of acetic acid. Naloxone + extract (150mg/kg)   signi.cantly increased the number of writhing. From the results it could be concluded that the Calendula Of.cinalis extract exhibits anti-nociceptive activity. Analgesic effects of Calendula Of.cinalis have the same pathway as opioids, but just in the peripheral test (acetic acid-induced writhing test).